Caring for groundwater: How care can expand and transform groundwater governance - Zwarteveen, Margreet; Domínguez-Guzmán, Carolina; Kuper, Marcel; Saidani, Amine; Kemerink-Seyoum, Jeltsje; Cleaver, Frances; Kulkarni, Himanshu; Bossenbroek, Lisa; Ftouhi, Hind; Verzijl, Andres; Aslekar, Uma; Kadiri, Zakaria; et al. (Ubiquity Press, Ltd., 2024)
Efforts to measure and regulate groundwaters and irrigators are notoriously ineffective. The starting point of this article, therefore, is to question the continued faith in techno-managerial solutions to groundwater depletion. We discuss the potential of the conceptual vocabulary of ‘care’ to complement, refresh and expand ways of talking about and doing groundwater governance. Mobilizing a diverse range of examples from places where pressures on aquifers are particularly acute, we do this by exploring what care entails in everyday practices of groundwater use and management. We show that foregrounding care nuances and sometimes challenges stories of users unavoidably depleting aquifers when given the chance and means to do so. Irrigators may display concern about the longer-term sustainability of the aquifers on which their livelihoods depend, even when their own pumping practices are unsustainable. In spite of pressures to intensify and individualize, farmers sometimes do hold on to or creatively develop collective rules to fairly share groundwater and use it sustainably, complementing strategies to make do with what is available with investments in conservation and recharge. Attention to care, moreover, highlights the ongoing processes of tinkering that governing groundwater always entails. The ability to tinker hinges on intimate and often embodied knowledge of a watery place. Accepting the care involved in governing groundwater, our analysis therefore concludes, prompts a re-consideration of what is and who has water expertise, with important implications for the role of ‘outside’ experts. More than a new theory, we propose embracing care as an analytical sensibility, with the study of practices of care serving as one promising way to widen the conceptual and political space for understanding and doing human-groundwater relations.